Hydhrochemical Variations And Toxicological Risks Of Arsenic And Chromium In The Ganga River Ecosystem: A Seasonal Assessment At Brijghat - Kumar, Ajay; Anand, Bharti; Singh, Richa; Kumar, Jagdeesh; Garg, Vandana (International Journal of Aquatic Research and Environmental Studies, 2026)
This study evaluates the seasonal dynamics of the physicochemical properties and heavy metal contamination (Arsenic and Chromium) of the Ganga River water at Brijghat, Uttar Pradesh, India, over a two-year period (2018 2020). Water samples were systematically monitored across three distinct seasons: summer, monsoon, and winter. High-precision analytical techniques, including Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and HACH digital instrumentation, were utilized for quantification. Significant temporal variations were seen in all hydrochemical indices according to the empirical results. The pH of the river water was somewhat alkaline, increasing in the summer (8.20–8.51) and falling in the monsoon (7.07–7.13). Water temperature and dissolved oxygen (DO) showed a strong inverse relationship, with DO peaking in winter (9.65–10.05 mg/L) and falling to critical lows in summer (4.90–5.65 mg/L), which coincided with higher levels of chemical and biochemical oxygen demand (BOD: 6.50–6.85 mg/L and COD: 11.75–12.05 mg/L). The monsoon season saw high values for turbidity (5.34–5.69 NTU), total dissolved solids (TDS: 658.30–679.80 mg/L), total hardness, chloride, and phosphate due to severe soil erosion, geogenic leaching, and agricultural runoff. According to toxicological analysis, arsenic levels reached a maximum of 10.388 ppb during the monsoon, above the stringent WHO safety standard of 10 ppb for drinkable water. The total chromium levels varied from 8.820 ppb to 10.328 ppb, demonstrating a dual exposure mechanism caused by low-dilution winter circumstances and monsoonal runoff. In the end, these results demonstrate severe geogenic and anthropogenic stress on the river ecology, offering an essential scientific foundation to support sustainable water resource management in the area and improve future remediation measures.